Fortidens fremtid: historien om scenekunstarkivet Sceneweb - Leinslie, Elisabeth (Teatervitenskapelige studier, 2019)
Performing art is part of our national cultural heritage and in Norway we have good traditions for preserving the cultural heritage. For many years, however, performing arts was an art field where cultural heritage work was weak. During the last 10–15 years, this work has been strengthened. In this article, I will give an introduction to the work of a national digital performing arts archive that was developed during this period: Sceneweb – which is owned and operated by Performing Arts Hub Norway (PAHN). The Sceneweb database is a professional system adapted for the classification of performing art material. It is an object-based relational database which can function as an authority register and national standard for the recording of performing art material. In this article, I outline the choices that lie behind the development of this system, and for our national plan for the preservation and dissemination of archival material. I also explain our extensive cooperation with the National Library.